2023
DOI: 10.1186/s12889-023-14982-8
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of acute otitis media from 2003 to 2019 in children ≤ 17 years in England

Abstract: Background The 7-valent pneumococcal conjugate vaccine (PCV7) was introduced in 2006 and the 13-valent pneumococcal conjugate vaccine (PCV13) in 2010 in the UK. PCVs are active immunization for the prevention of invasive disease, pneumonia and acute otitis media (AOM) caused by Streptococcus pneumoniae in children. The aim of this observational study was to estimate incidence rates (IRs) of AOM in children ≤17 years from 2003 to 2019 in England, before and after the introduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Our study can serve as a valuable complement to the limited data of OM, while is important to adequately assess the interventions aimed at reducing its health, social and economic burden. We found that the annual incidence rate of OM in underfives in China was 11.32 per 100 person-years, which is comparable to studies from England (7.95 per 100 person-years), 21 Brazil (9.57 per 100 person-years), 22 America (14.98 per 100 person-years) 13 and the Netherlands (15.3 per 100 person-years), 23 and suggests the validity of our result. However, our estimated OM incidence rate was relatively lower than studies from Europe (25.6 per 100 person-years), 24 possibly due to different case definitions, study designs and healthcare policies.…”
Section: Discussionmentioning
confidence: 77%
“…Our study can serve as a valuable complement to the limited data of OM, while is important to adequately assess the interventions aimed at reducing its health, social and economic burden. We found that the annual incidence rate of OM in underfives in China was 11.32 per 100 person-years, which is comparable to studies from England (7.95 per 100 person-years), 21 Brazil (9.57 per 100 person-years), 22 America (14.98 per 100 person-years) 13 and the Netherlands (15.3 per 100 person-years), 23 and suggests the validity of our result. However, our estimated OM incidence rate was relatively lower than studies from Europe (25.6 per 100 person-years), 24 possibly due to different case definitions, study designs and healthcare policies.…”
Section: Discussionmentioning
confidence: 77%
“…This is similar to the prevalence in other African countries and higher than the prevalence rates in developed countries such as Norway, England, and the United States, probably due to better pneumococcal conjugate vaccination rates in the developed world. [25][26][27][28][29] Although mostly ignored and under-looked by most physicians, acute otitis media, which is the inflammation of the structures of the middle ear, is common and associated with longterm complications such as hearing loss when diagnosis and treatment are delayed. 26,30 Outpatient diagnosis is possible through visualization of inflammation or whitish discharge in an outpatient visual inspection using an otoscope.…”
Section: Dovepressmentioning
confidence: 99%
“…d Mohanty et al [ 21 ] (for ages 0–17 years); and HES (for ages ≥18 years) [ 24 ]. e Mohanty et al [ 25 ] (for ages 0–17 years); and The Health Improvement Network (THIN) database (for ages ≥18 years) [ 26 ]. f Mohanty et al [ 25 ] (for ages 0–17 years); and THIN database (for ages ≥18 years) [ 26 ].…”
Section: Figurementioning
confidence: 99%
“…e Mohanty et al [ 25 ] (for ages 0–17 years); and The Health Improvement Network (THIN) database (for ages ≥18 years) [ 26 ]. f Mohanty et al [ 25 ] (for ages 0–17 years); and THIN database (for ages ≥18 years) [ 26 ]. g Mohanty et al [ 21 ] (for ages 0–17 years); and Miller et al [ 27 ] (for ages ≥18 years).…”
Section: Figurementioning
confidence: 99%